ANALYSIS SYSTEM KEY PERFORMANCE INDICATORS OF FILLING - Vitaly Komlev; Robert Nizhegorodtsev; Alexander Nosov (Вестник Северо-Кавказского федерального университета)
The paper gives an analysis of the key performance indicators of the recruitment process in the enterprise. There are proved some factors influencing the efficiency of different types of selection - profitability (resource productivity), effectiveness and operability. There are given some practical issues illustrating validity of each factor for decision making in recruitment execution. There is invented an approach for a comprehensive assessment of the efficiency of recruitment in the company. The paper discusses contemporary trends in efficiency evaluation concerned the increasing role of intellectual capital in a process ofproduction.